The Analysis Of Students' Speaking Ability To Describe New Vocabularies With Difference Social Media Exposure At SMA Negeri 2 Perbaungan In The Academic Year Of 2021-2022 - Nadia Ayu Mulani; Nurhafni Siregar (Pusdikra Publishing, 2022)
Most students of SMA Negeri 2 Perbaungan face many difficulties to communicate in English. Their lack of vocabulary, lack of grammar and fear of making mistakes and this affect speaking performance of students. The objective of this research was to investigate the students’ speaking ability to describe new vocabulary with difference social media exposure. This observation was taken two days which started from Thursday, 12th May and 19 May 2022. The qualitative research method was used in this research. The subjects of this research chosen based on the result of observation sheet and interviewed eight student as the representative of students in the first grade of SMA Negeri 2 Perbaungan, academic year 2021-2022. The population from this research were the whole students in the 1st grade SMA Negeri 2 Perbaungan. The data collection technique used was observation and test using observation sheets designed with Madsen's theory (1983) to determine the abilities achieved by students, from all research data found 8 research subjects with 4 indicators/elements namely pronunciation, vocabulary, fluency and grammar. After doing the research, it was found that there were 4 students who were active on social media, they had about 8-10 hours per day to use social media. They have 3 levels of speaking ability, namely high, medium and less, 2 students who have a high level of ability are not perfect in describing new vocabulary, 1 student who is moderate still not precise in pronouncing the sentence to be spoken. And 1 student who has a poor level has difficulty in describing new vocabulary. On the other hand, the researcher also found 4 students who were not active on social media, they only used social media 5 hours per day. They have 3 levels of speaking ability, 1 student with a high level cannot describe well, 1 student with a moderate level also has a deficiency in describing vocabulary and 2 students with a bad level are very difficult to describe new vocabulary. In addition, the researcher also found 3 levels of student motivation with different social media exposure, high student motivation there is no parental control over the use of social media as well as moderate student motivation. And students who have low motivation because of parental control over the use of social media. The results of this research, students' speaking ability is not significant to social media and parental control is needed in the use of social media.